A Selective Medium for Screening Ceftazidime/Avibactam Resistance in Carbapenem-Resistant Enterobacterales - Zeng, Weiliang; Liao, Wenli; Zhao, Yajie; Wang, Lingbo; Shu, Hongyun; Jia, Huaiyu; Chen, Tao; Zhang, Ying; Zhou, Tieli; Wu, Qing (Frontiers in Microbiology, 2022)
Ceftazidime/avibactam (CZA) is an alternative antibiotic used for the treatment of infections caused by carbapenem-resistant Enterobacterales (CRE). However, the CZA-resistant CRE strains have been detected worldwide. Therefore, it is critical to screen CZA-resistant CRE strains in colonized patients or a specific population so as to rapidly implement infection control measures to limit their transmission. In our study, we developed a Salmonella-Shigella (SS) CZA selective medium and assessed its performance to screen for clinical CZA-resistant CRE isolates in both pure-strain specimens and stool samples. A total of 150 non-duplicated isolates including 75 CZA-susceptible and 75 CZA-resistant CRE pathogens were tested by using the broth microdilution method and the SS CZA medium, respectively. The bacterial suspensions were serially diluted in the SS CZA medium, which showed excellent screening performance in both pure CZA-resistant CRE strain and the stool samples with the lowest detection limit of 101–102 CFU/mL and 101–103 CFU/mL, respectively. Notably, none of the susceptible isolates showed growth even at the highest dilution concentration of 108 CFU/mL. Most importantly, the SS CZA medium demonstrated excellent performance in screening simulated clinical polymicrobial specimens. Moreover, its screening performance was unaffected by the different resistance determinants for tested isolates. Cumulatively, our data suggest that the SS CZA medium can be used as a promising selective medium to screen CZA-resistant CRE, irrespective of their resistance mechanisms.